Experimental analysis on the effect of area of surface cooling for a water-cooled photovoltaic - Firdaus, Basrawi; Leon, Y. C.; Ibrahim, Thamir K.; Mohd Hazwan, Yusof; A. A., Razak; Shaharin Anwar, Sulaiman; Yamada, Takanobu (EDP Sciences, 2018)
Water flow for a water-cooled Photovoltaic (PV) may not cover the whole surface area of PV. Thus, the objective of this paper is to experimentally observe the effect of cooling surface area for a water-cooled PV. A water-cooled PV with 30W output was tested when its surface area was 50% and 100% covered with flowing water. This condition was tested at water flow rate of 120 mL/h, and irradiace of 855 W/m2, respectively. It was found that the panel recorded a maximum temperature of 72.10°C when it is uncooled. When it is cooled temperature decreased 22.05% and 51.04% for half and full surface, respectively, and temperature also remained constant approximately at 32oC for full surface. The current remained constant as expected and effect of temperature could be seen in voltage. Voltage increases when temperate decreases, and decreases when temperature increases. As the results, the power outputs for uncooled, half surface, and full surface were 10.38W, 10.66W and 11.08W, respectively. As compared to uncooled, this shows the increment of 6.10% and 13.50% for half surface and full surface, respectively. Thus, it could be concluded that the cooling surface area has substantial effects on the performance of water-cooled PV.